Frequent Contamination of Healthcare Worker Scrubs. (4th October 2017) - Escobar, Daniel; Thom, Kerri; Harris, Anthony; Zhan, Min; Johnson, J Kristie
Abstract: Background: Pathogens responsible for healthcare-associated infections (HAI) can be spread from patient-to-patient via healthcare worker (HCW) hand, clothing and other fomites. Methods: We performed a cohort study of HCWs in critical care areas to assess factors associated with bacterial contamination of scrubs. Participants were given one set of four new, study-issued scrubs along with a randomized schedule of wear at the start of the study. During an 8-month study period, each scrub set was sampled eight times, on random days and at least 4 hours into a shift. Sampling of scrubs was with a pre-moistened cotton swab in a W-shape over the front of the scrub top and along both thighs, as well as RODAC agar plate stamped over the top near the belly button. A brief survey tool was used to identify risk factors for contamination at the time of sampling. Total colony count and the presence of pre-specified, pathogenic bacteria ( Staphyloccocus aureus, Enterococci or Gram-negative bacteria) were assessed. Generalized estimating equation (GEE) was used to identify factors associated with bacterial contamination. Results: A total of 720 scrub samples were obtained from 90 HCW; 30% (217/720) of scrubs were contaminated with pathogenic bacteria. The mean (standard deviation) log colony count of the sampled scrubs was 3.9 (1.1). On sampling days, HCWs reported on average, primary care of 2.4 patients and interaction with 5.4 patients. Multivariate analysis showed that providing care for patients with wounds was associated with scrub contamination of pathogenic bacteria (OR 1.75, 95% CI: 1.17–2.62). The average log colony count was higher among HCWs who gave a patient a bath (log CFU difference = 0.21, P  = 0.05). Bacterial contamination was lower among HCWs assigned to care for at least one patient on Contact Precautions (CP) (log CFU difference = 0.28, P < 0.01). Conclusion: HCW attire is frequently contaminated with pathogenic bacteria. Contamination is associated with providing care for patients with wounds and giving a bath; while contamination is lower when caring for patients on CP. The later finding supports the use of CP to decrease potential risk of transmission. Disclosures: All authors: No reported disclosures.